Pemanfaatan Ilmu Pengetahuan dan Teknologi Dalam Kegiatan Pengabdian Masyarakat di Perguruan Tinggi Idris HM Noor - Idris HM Noor (Jurnal Pendidikan dan Kebudayaan, 2011)
The aims of this research are to find data and information about: 1) the policy of Directorate of Higher Education (DHE) and universities related to its function on the public service; and 2) the implementation of research and development based on the study result. The research was conducted from June to December 2009. Research sample is 36 respondents in HE at the provinces of DIY, West Java, West Nusa Tenggara, Bali, East Kalimantan, West Kalimantan, Lampung, West Sumatera, and North Sumatera. Data was collected by using questionnaire, study documentation, and interview. Data was analyzed using quantitative and qualitative analysis. Research findings are: The policy of research and public service done by universities is based on the policy of DHE. DHE still makes very few policies of the research for public service and lack of monitoring and evaluation of the universities’ program.